Effectiveness of Numeracy Intervention Program in Improving Basic Mathematical Skills among Non-Numerate Students - Pondevida, Melinda (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of the Numeracy Intervention Program in improving basic mathematical skills among non-numerate Grade 7 students at Tomas Claudio Colleges, Morong, Rizal. Utilizing an experimental research design, specifically a single-group pretest–posttest approach, the study aimed to determine whether structured numeracy interventions significantly enhance learners’ mathematical performance. The respondents were described in terms of age, sex, sibling position, family size, parents’ educational attainment, occupation, and monthly income. Data were gathered through validated assessment tools and analyzed using mean, standard deviation, paired t-test, and analysis of variance (ANOVA).Findings revealed that most respondents were 13-year-old male students from medium to large families and belonged to lower-middle to middle-income households. Prior to the intervention, learners demonstrated low mathematical performance with a mean score of 10.70. After exposure to the Numeracy Intervention Program, results showed a marked improvement with a mean score of 19.42, indicating that all participants reached at least a satisfactory level. The decrease in score variability further suggested more consistent learning outcomes. The paired t-test confirmed a statistically significant difference between pretest and posttest scores, establishing the effectiveness of the intervention. ANOVA results indicated that socio-demographic variables such as age, sex, sibling position, family size, and parents’ education and occupation did not significantly influence posttest performance. However, monthly family income showed a significant effect on learner improvement.The study concludes that the Numeracy Intervention Program is effective in enhancing basic mathematical skills among non-numerate students and is applicable across diverse learner backgrounds. It is recommended that schools integrate structured intervention programs into the mathematics curriculum, strengthen teacher training, and enhance parental support to sustain learner progress and improve numeracy outcomes.Implications for policy and classroom practice are also discussed in relation to equitable learning outcomes in education